2022
DOI: 10.3390/pharmaceutics14071312
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of the 3D-Printed Drug Delivery Systems: A Review

Abstract: Since the appearance of the 3D printing in the 1980s it has revolutionized many research fields including the pharmaceutical industry. The main goal is to manufacture complex, personalized products in a low-cost manufacturing process on-demand. In the last few decades, 3D printing has attracted the attention of numerous research groups for the manufacturing of different drug delivery systems. Since the 2015 approval of the first 3D-printed drug product, the number of publications has multiplied. In our review,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 190 publications
0
26
0
Order By: Relevance
“…Additionally, the mass loss observed at these temperatures was less than 2%, indicating good thermal stability, which is important for proper storage and handling of the inks. While other authors have used various 3DP methods to obtain sublingual delivery forms [ 42 ], it was observed that mass loss could exceed 10% at the higher temperatures used in other 3D printing methods, such as fused deposition modeling (FDM). This suggests that the properties of the ink and the nanocrystals containd within it could be compromised during this type of 3DP process.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the mass loss observed at these temperatures was less than 2%, indicating good thermal stability, which is important for proper storage and handling of the inks. While other authors have used various 3DP methods to obtain sublingual delivery forms [ 42 ], it was observed that mass loss could exceed 10% at the higher temperatures used in other 3D printing methods, such as fused deposition modeling (FDM). This suggests that the properties of the ink and the nanocrystals containd within it could be compromised during this type of 3DP process.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, deposition of polymer-based layers are believed to cause complications, such as loosening from the implantation site, changes in chemical composition in physicochemical media, and likely side effects due to the corrosion products [ 34 , 35 ]. For this reason, many researchers have been investigating the use of inorganic coatings as drug delivery systems [ 36 ]. There has been little attention given to metallic drug eluting systems in comparison with polymeric systems.…”
Section: Introductionmentioning
confidence: 99%
“…3D printing, on the other hand, has gained signi cant attention as a progressive innovation in the pharmaceutical eld and is expected to revolutionalize drug manufacturing 23 . Its use has expanded exponentially in recent years due to its potential advantages, including producing a personalized dose form with a speci c shape, modi ed release kinetics, and color thereby ensuring patient-centricity [24][25][26] . Furthermore, 3D printing is able to produce a high-quality product, within minutes, saving time and resources 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Its use has expanded exponentially in recent years due to its potential advantages, including producing a personalized dose form with a speci c shape, modi ed release kinetics, and color thereby ensuring patient-centricity [24][25][26] . Furthermore, 3D printing is able to produce a high-quality product, within minutes, saving time and resources 24 .…”
Section: Introductionmentioning
confidence: 99%